Values and administrative practices for generations associated with organizational innovation (2021)
Generational analysis and studies are a recent research trend that analyzes social, cultural, political, and economic changes within the framework of the digital revolution. In this work, an approach is made to the generational phenomena in the SMEs. The objective is to identify the correlations between entrepreneurship and management operations from the logic of individual values and the practices of SMEs managers and owners in Bogotá, from the Blackman model, according to their correspondence with the generational classification taking into account your date of birth. The sample is 383 entrepreneurs from Bogotá, and it was found that there are significant differences associated with generations in skills and abilities, risk management, honesty, responsibility, and work in the provision of services and facilities.